Exploring staff perception of corporate governance practices of Universities in Ghana (Journal of Educational Management, 2023)
Corporate governance practices of institutions such as universities have the impetus to influence the level of staff contentment. The study sought to explore staff contentment with the corporate governance practices of universities in Ghana. It adopted a qualitative phenomenological design and involved nine autonomous public universities and four autonomous private universities. A purposive sampling technique was employed to select 24 staff who represent pro-vice-chancellors (academic) and registrars for in-depth interviews, while focus group discussions were conducted with 95 staff, which were composed of senior members (academic), senior members (non-academic), senior staff, and junior staff. Data were collected using a semi-structured interview guide. The data were analysed using Interpretative Phenomenological Analysis. It was found that the staff of universities are content with almost all corporate governance practices of the universities except council size, composition, and the election of deans of faculty. To make sure that every member of staff is adequately represented on the councils through their unions, it is recommended that the management of universities, via the Minister of Education, review the statutes addressing the size and composition of the institutions. Moreover, it is recommended that universities institutionalize training programmes for all staff to prepare them to occupy leadership and management positions in the future. In conclusion, the existing policy regarding the election of the deans of faculty should be substituted with an appointment based on an individual's experience and qualifications.Key Words: Corporate governance practices, staff contentment, autonomous universities, private universities, and public universities
Keywords: Corporate governance practices; staff contentment; autonomous universities; private universities; public universities